Evaluation of tendered prices of natural mineral water, juice and non-alcoholic beer (public procurement research) - Nataša Pomazalová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
The purpose of this paper is to evaluate tender prices of chosen beverages according to public procurement based on secondary data analysis. The empirical results of analysis (t-test and F-test) show that average annual prices of these beverages are different and collected data are not included in the same sample. Tender prices are different in each year of observed years, although are based on public tender. Important evidence is that for the public tenders in the abroad is obligatory use of the Czech public procurement law. According to this act the base evaluation criterion is the lowest offered price. Data were collected during the years 2005–2009. This study deals with empirical approach, variability of prices of chosen beverages based on public tenders between the Czech Republic (Ministry of Defence) and local suppliers in Kosovo. Results show low variability of prices, which are based on public tender and legal approach, regulated public procurement. The research conclusion is the fact, that tender prices for piece of non-alcoholic beverage are less than 10 % from annual mean (pcs./CZK) of tendered prices.